ASSESSING THE ROLE OF THIRD-PARTIES INTERVENTION IN FARMER-HERDER CONFLICT IN KWARA STATE, NIGERIA - Idowu, S.A.; Akinsola, G.O.; Tomori, R. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study assessed the role of third-parties intervention in farmer herder conflict in Kwara State, Nigeria. Purposive sampling was used to select 400 respondents. Thus, in-depth interviews and semi-structured questionnaires were used to elicit data from respondents. The collected data was subjected to descriptive (frequency counts and percentage) and Likert scale statistical analysis. The study revealed that the major causes of farmers-herders conflict were encroachment on farmland/cattle routes, criminality perpetrated by farmers and herders, and climate change’s impact. The study identified the deployment of security operatives to the conflict zones peace mediation by community leaders. The findings reveal that third-party interventions led by government, traditional leaders, and civil society organizations have been largely ineffective in addressing the root causes of the conflict. While community-led mediation was perceived as fairly effective (48.7%), government peace committees (47.6% ineffective) and security interventions (59.3% ineffective) failed to de-escalate tensions. Litigation and relief distribution by NGOs also showed limited success. The study identifies open grazing, climate change, and criminal activities as major drivers of the conflict, with respondents highlighting the need for ranching, legislative reforms, and regular peacebuilding initiatives. The study concludes that third-party interventions have eased but not resolved the conflict, as underlying issues such as resource scarcity, ethnic tensions, and inadequate institutional frameworks remain unaddressed. Therefore, the study recommended that herders embrace ranches to separate farmlands from the grazing animals and, thus, eliminate the crisis.